Perturbations to Al-27 electric field gradients in nanocrystalline alpha-Al2O3 studied by high-resolution solid-state NMR - Sabarinathan, V.; Ramasamy, S.; Ganapathy, Subramanian (Journal of Physical Chemistry B, 2010)
Al-27 solid-state NMR has been employed to study the perturbations to Al-27 electric field gradients for the aluminum environments in nanocrystalline alpha-alumina. Triple quantum magic angle spinning experiments show that the octahedral aluminum coordination remains unchanged down to 12 nm, although severe perturbations to Al-27 electric field gradients are noticed at 28 nm and below. 3Q-MAS and SATRAS experimental data of nano alpha-alumina have been analyzed through extensive spectral simulations to probe Al-27 electric field gradients of aluminum in the grains and grain boundaries. While the aluminum in the grains has a unique field gradient tensor, the same octahedrally coordinated aluminum environments in the grain boundaries suffer a distribution of electric field gradients. This is evidenced by data analysis of both 3Q-MAS and SATRAS spectra. By invoking the Gaussian isotropic model, in which the (C-Q, eta(Q)) parameter space is discretely sampled by the Czjzek distribution, we have been able to analyze the Al-27 SATRAS spectra of nanocrystalline alpha-alumina samples having grain sizes of 52, 28, 20, and 12 nm. Good agreement between experimental and simulated spectra has led to the quantitative determination of grain and grain boundary components in these materials.